Le modèle de la firme-réseau : innovation ou réinvention anglo-saxonne ? - Olivier de Gromard (Revue LISA)
Since the early 1980s, the network company has become more widespread as it is considered the most appropriate organisational structure in a global economy. It is commonly agreed that this type of organisation is an Anglo-Saxon model. The aim of this article is to give some insights into this current opinion, through two complementary analyses: the first one investigates the link between the innovative boost in Anglo-Saxon countries and the creation of the network company model; the second one considers the role of traditional Chinese capitalism in the exceptional economic success of Hong Kong under British sovereignty.